New onset of sinoatrial block in a young patient treated with systemic meglumine antimoniate. Issue 3 (16th January 2021) - Daadaa, Najla; Youssef, Soumaya; Haggui, Abdeddayem; Harbaoui, Sarra; Jaber, Kahena; Doss, Nejib; Dhaoui, Mohamed Raouf
Abstract: The sinoatrial block is a new side effect of meglumine antimoniate. Prompt interruption of the drug results in the normalization of electrographic changes and prevents sudden cardiac arrest. Abstract : The sinoatrial block is a new side effect of meglumine antimoniate. Prompt interruption of the drug results in the normalization of electrographic changes and prevents sudden cardiac arrest.